Ccdc103 promotes myeloid cell proliferation and migration independent of motile cilia - Falkenberg, Lauren G. (Dis Model Mech, 2021)
The pathology of primary ciliary dyskinesia (PCD) is predominantly attributed to impairment of motile cilia. However, PCD patients also have perplexing functional defects in myeloid cells, which lack motile cilia. Here, we show that coiled-coil domain-containing protein 103 (CCDC103), one of the genes that, when mutated, is known to cause PCD, is required for the proliferation and directed migration of myeloid cells. CCDC103 is expressed in human myeloid cells, where it colocalizes with cytoplasmic microtubules. Zebrafish ccdc103/schmalhans (smh) mutants have macrophages and neutrophils with reduced proliferation, abnormally rounded cell morphology and an inability to migrate efficiently to the site of sterile wounds, all of which are consistent with a loss of cytoplasmic microtubule stability. Furthermore, we demonstrate that direct interactions between CCDC103 and sperm associated antigen 6 (SPAG6), which also promotes microtubule stability, are abrogated by CCDC103 mutations from PCD patients, and that spag6 zebrafish mutants recapitulate the myeloid defects observed in smh mutants. In summary, we have illuminated a mechanism, independent of motile cilia, to explain functional defects in myeloid cells from PCD patients. This article has an associated First Person interview with the first author of the paper.